Effects of adding silver carp Hypophthalmichthys molitrix protein concentrate on sensory, texture and cooking properties of pasta and its shelf life - Mahsasadat Mousavi Sane; Seyedeh Zahra Mirhosseini Roudbaraki; Mohammad Ali Nematollahi; Seyed Vali Hosseini (تغذیه آبزیان)
Introduction: Pasta is one of the relatively wide-consumed flour products in Iran, however despite its abundant consumption, it lacks some nutrients, especially some essential amino acids. On the other hand, fish protein concentrate (FPC) is a suitable option for enriching pasta due to its high amount of protein. It is a healthy product with high nutritional value in which protein and other nutrients are compactly placed. Therefore, in this study, the effects of adding the silver carp Hypophthalmichthys molitrix protein concentrate as one of the food supplements rich in amino acids on improving pasta's nutritional value and sensory, textural, and physicochemical properties was investigated. Materials and methods: In this study, three types of pasta were formulated with different concentrations of 0, 1, and 2% FPC (T0, T1% and T3% respectively). T0 consisted of ingredients such as No. l flour, water, gluten, and salt, was formulated. In T1% and T3%, flour was replaced by 1 and 2% FPC, respectively. The effects of adding FPC to pasta on its sensory (flavor, smell, taste, and color), textural (adhesion, hardness, and flexibility), and physicochemical (cooking time, water absorption percentage, swelling index, and cooking loss) properties were investigated. Results and discussion: The obtained results showed no significant difference in the sensory characteristics between the three treatments, and also the results exhibited the decrease in some textural characteristics of the produced pasta, such as the amount of adhesion, hardness, and flexibility with the addition of protein concentrate, so that the lowest amount of adhesion was observed in T2%. In terms of cooking time and the amount of cooking loss, the control treatment (T0) showed the highest value, while water absorption percentage and swelling index, by the elevation in the amount of concentrate, the value of these two also increased (p < 0.05). Conclusion: Based on the results, the pasta enriched with 2% FPC, along with improving the nutritional value, improved several properties, including adhesion while no significant alteration in sensory properties.